Gingival Condition and Enamel Defect Among Secondary School Female Students in Kirkuk City/Iraq - Ibrahim, Jihan A.; Hussien, Baydaa (Journal of Baghdad College of Dentistry, 2018)
Background: Gingivitis is one of the most common and widely spread oral diseases in adolescents after dental caries occur in both developed and developing countries. Dental plaque is the main etiological factor of gingivitis. Another oral problem is enamel defect. The aim of this study was to estimate the oral hygiene (dental plaque), and determine the prevalence and severity of gingivitis and enamel defects among 16-17 years old secondary school female students in urban areas of Kirkuk city/Iraq. Materials and methods: A representative sample included in this study consisted of 750 secondary school female students distributed into 387 for the age sixteen and 363 for the age seventeen, they were selected randomly from different female secondary schools in the urban areas of Kirkuk city. Dental plaque was assessed using plaque index of Silness and Loe (1964). The gingival health condition was assessed using gingival index of Loe and Silness (1963), while, enamel anomalies was determined following the criteria of WHO. Results: The mean value of plaque index for the total sample was 0.92Â±0.02. The prevalence of gingivitis was (88.53%) and the mean value of gingival index was 0.90Â±0.02. Regarding age, the mean value of gingival index increased with age with statistically no significant difference (P>0.05). There was a strong positive and statistically highly significant correlation between plaque and gingival indices for total sample and for both ages (P